EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN TIME TOKEN UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI SMP NEGERI 1 ANGKOLA SANGKUNUR - Siska Perawati (JURNAL MathEdu (Mathematic Education Journal), 2019)
ABSTRACT This study aims to describe the effectiveness of using time token learning model to increase students’ mathematical problem solving ability on the topic equation system of two variablesat the eighth grade students of SMP Negeri 1 Angkola Sangkunur. The research was conducted by using quasi experimental method (pretest post test one group design) with 30 students as the sample and they were taken by using purposive sampling technique from 62 students. Test and questionnaire were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using time token learning model was 2.60 (good category) and (b) the average of students’ mathematical problem solving ability equation system of two variables before using time token learning model was 58.83 (fair category) and after using time token learning model was 71.66 (good category). Furthermore, based on inferential statistic by using paired sample ttest and helping SPSS version 16, the result showed the significant value was less than 0.05 (0.000<0.05). It means, time token learning model was effective was used to increase students’ mathematical problem solving ability equation system of two variables. Keywords: learning model, time token, mathematical problem solving ability